Economics as Institutionally Formed Process - Карл Поланьи (Journal of Economic Sociology, 2010)
This is the first part of one of the main texts by Karl Polanyi about the two meanings of “economic”. No doubts,  Polanyi is the classic and widely cited author in economic sociology. Now we can watch therenaissanceof his papers both in Europe and the USA. In 2001 a new edition of his book of “Great transformation” was published with the introduction by J.Stigliz and F.Block. In Russia Polanyi is not so popular, however two translations from his books were published (in THESIS and in the book by T. Shanin “Informal Economy”). The translation of the “Great Transformation” is not finished yet. The full version of this translation will be given in the reading book “Western Economic Sociology”.